The Feminine in the Structure of the Arabic Language: An Analytical Semantic Study - Usama Hammad (IJAS: Indonesian Journal of Arabic Studies, 2022)
This research aims to shed light on the feminine in the structure of the Arabic language including its letters and diacritics, utterances and structures to pinpoint the deep role of feminine signs and semantics in the structure of the Arabic language. This study is on a mission to show that the feminine in Arabic is not only one of its major pillars and most authentic landmarks, but it also profoundly exhibits its strength and beauty. The study also seeks to explore the clear harmony between the Islamic Sharia and the Arabic language, as mainly reflected in the structures, connotations and use of the feminine in Arabic. The researcher underscores the need for further research on the role of the feminine and its signs and features in the formation of the Arabic language, so as to highlight the interesting research horizons of this direction of linguistic studies.يهدف في هذا البحث إلى تسليط الضوء على المؤنّث في بنية اللغة العربيّة، في حروفها وحركاتها، وألفاظها وتراكيبها، لِما لمسنا من دور عميق لعلامات التأنيث ودلالاته في بنية هذه اللغة، للدرجة التي ترقى إلى أنْ تكون ركنًا كبيرًا من أركانها، ومعلمًا أصيلًا من أهمّ معالمها، وسرًّا عميقًا من أهم أسرار قوّتها وجمالها. ونسعى_ أيضًا_ إلى الإشارة إلى ما انكشف لنا من انسجام واضح بين الشريعة الإسلاميّة واللغة العربيّة؛ مستندين إلى أدلّة بيِّنة واضحة من غير الاعتماد على البعد العقائدي والدينيّ لكوننا مسلمين. وداخلَنا إيمان عميق بالحاجة إلى مزيد فحص لدور المؤنّث وعلاماته ومعالمه في تكوين هذه اللغة، وبخاصّة لِما لا نزال نلمسه بين الفينة والأخرى بسبب التفاعل معَ هذه اللغة، ولِما نراه من علامات على تلك الآفاق البعيدة لهذا المنحى من الدراسات اللغويّة، ونرجو أنْ يكون هذا البحث محطّة في هذا الطريق.